Intensive care nurses' experiences with the new electronic medication administration record - Linda R. Gregory; Rimen Lim; Lois MacCullagh; Therese Riley; Karen Tuqiri; Jan Heiler; Kath Peters (Wiley, 2022)
Abstract Aim To explore the experiences of Registered Nurses who administered medications to patients using the electronic medication administration record (eMAR) in Electronic Record for Intensive Care (eRIC) at one adult intensive care unit (ICU) in NSW, Australia. Design The study research design used a qualitative descriptive exploratory approach that took place in two stages. Methods Five participants attended one focus group followed by the observation of each participant as medications were administered to their assigned patient using the eMAR in eRIC. Results From the data, three themes and one subtheme were identified. Themes included forcing nurses to work outside legal boundaries; patient safety; with a subtheme titled experiencing computer fatigue; and taking time away from the patient. To practise safely, nurses were required to implement workaround practices when using the new eMAR in ICU. Nurses also were concerned that the eMAR in eRIC took time away from the patient at the bedside and 'added more screen time' to their day.